Post-specimen encounters between art, science and curating : rethinking art practice and objecthood through scientific collections - Juler, Edward; Robinson, Alistair (Intellect, 2020)
Examines how scientific objects in museums and other collections act as inspiration to contemporary art practice, its histories, curating and aesthetics. Cross-disciplinary essays from leading arts professionals explore how scientific encounters in museums provoke new modes of creative thinking about art, science and curating. 84 col. illus.